Treatment of diarrhea in young children: Results from surveys on the perception and use of oral rehydration solutions, antibiotics, and other therapies in India and Kenya - Greg Zwisler; Evan Simpson; Melissa Moodley (Edinburgh University Global Health Society, 2013)
Diarrheal disease is a leading cause of morbidity and mortality among children under five. Although oral rehydration solution (ORS) has tremendous therapeutic benefits, coverage of and demand for this product have remained low in many developing countries. This study surveyed caregivers and health care providers in India and Kenya to gather information about perceptions and use of various diarrhea treatments, assess reasons for low ORS use, and identify opportunities for expanding ORS use.